2022
DOI: 10.3389/fonc.2022.970557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on postoperative systemic inflammation and recovery in patients undergoing digest tract cancer surgery: A meta-analysis of randomized controlled trials

Abstract: Perioperative immune function, postoperative cognitive function and prognosis are momentous issues for patients undergoing digestive tract cancer surgery. Studies have investigated the efficacy of dexmedetomidine (DEX) administration on these issues, but the results are inconsistent. Therefore, this meta-analysis aimed to summarize all the existing evidence and draw a conclusion more accurately on these associations. Trials were located through electronic searches of the PubMed, Embase, the Cochrane Library an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Finally, we found that intraoperative dexmedetomidine treatment reduced the length of hospital stay and the incidence of postoperative pulmonary complications. Although the sensitivity analysis and TSA revealed these results to be inconclusive, they were highly consistent with those of other meta-analyses [ 36 , 40 ]. Based on the results, the mechanisms by which dexmedetomidine improves oxygenation and pulmonary function during OLV can be speculated.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, we found that intraoperative dexmedetomidine treatment reduced the length of hospital stay and the incidence of postoperative pulmonary complications. Although the sensitivity analysis and TSA revealed these results to be inconclusive, they were highly consistent with those of other meta-analyses [ 36 , 40 ]. Based on the results, the mechanisms by which dexmedetomidine improves oxygenation and pulmonary function during OLV can be speculated.…”
Section: Discussionsupporting
confidence: 89%
“…Two meta-analyses indicated that DEX administered during cancer surgery reduced the secretion of protumorigenic inflammatory cytokines such as IL-6 and TNF-α but increased the levels of circulating T cells. It should be noted that not all included RCTs have investigated DEX-mediated immunomodulation and its consequences on immunosurveillance 59 , 60 ( Figure 4 ). Very few RCTs aimed to evaluate the impact of DEX on recurrence-free survival or overall survival, yielding mostly inconclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…Both meta-analyses concluded on a DEX-induced decrease in protumor and inflammatory cytokines such as CRP, IL-6, IL-8 and TNF-α. 59 , 60 Many other studies dealing with the surgical removal of various solid primary tumors demonstrated that patients receiving intravenous DEX during the perioperative period had an attenuated increase in glucocorticoid stress compared to the control group. 61–70 Interestingly, two trials observed that DEX affected the activity of the corticotropic axis by attenuating the concentrations of circulating catecholamines and adrenocorticotropic hormone (ACTH).…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al performed a similar meta-analysis of dexmedetomidine in 2023, which also included data on MMSE testing of post-operative patients to evaluate cognitive functioning (220). The researchers found that there was a significant reduction in POCD occurrence at 12 h, 24 h and 72 h post-surgery (244). Another meta-analysis focused solely on cognitive function, which was evaluated through MMSE testing of post-operative elderly patients, found that dexmedetomidine had a preventative effect on the incidence of POCD (245).…”
Section: Dexmedetomidinementioning
confidence: 99%